Swarm intelligence algorithms : modifications and applications - Slowik, Adam (CRC Press, Taylor & Francis Group, 2021)
"This book presents 24 swarm algorithms together with their modifications and practical applications. Each chapter is devoted to one algorithm. It contains a short description along with a pseudo-code showing the various stages of its operation. In addition, each chapter contains a description of selected modifications of the algorithm and shows how it can be used to solve a selected practical problem"- Resumé vydavatel
First edition published 2020
Keywords: inteligence hejna; algoritmy; matematická optimalizace; swarm intelligence; algorithms; mathematical optimization; kolektivní monografie; collective monographs